Polymer, antifriction agent for lubricating oil, and lubricating oil composition
By using (meth)acrylic graft copolymer with main chain and side chain structure as a wear reducer in lubricating oil, the problem of poor effect of the existing wear reducer is solved, efficient friction reduction and low viscosity maintenance are achieved, and the service life of the machine is extended.
Patent Information
- Application Number
- CN202380063011.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-11
AI Technical Summary
The wear reducing agent used in existing lubricants is insufficient in reducing friction, and the low viscosity lubricants lead to an increase in friction load, which in turn affects the life of the machine.
A (meth)acrylic graft copolymer having a main chain polymer structure and a side chain polymer structure is used as a wear reducer. The polymer is added to the lubricating oil to form a low viscosity lubricating oil composition.
It improves the wear reduction effect of lubricating oil, reduces the friction coefficient, and maintains low viscosity, thereby extending the service life of the machine and saving fuel consumption.
Smart Images

Figure BDA0005291482840000041 
Figure BDA0005291482840000071 
Figure BDA0005291482840000141
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer used in lubricating oil, a friction reducing agent for lubricating oil, and a lubricating oil composition.
[0002] This application claims priority based on Japanese Patent Application No. 2022-143800 filed in Japan on September 9, 2022, and the contents are incorporated herein by reference. Background Art
[0003] Various antifriction agents are added to lubricating oils such as automobile engine oils and drive train oils to reduce energy loss caused by friction and extend the life of the machine by preventing seizure. In recent years, as lubricating oils have become less viscous in order to save fuel, the load on the contact surface between metals has increased dramatically, and the role of antifriction agents has become more important.
[0004] As antifriction agents, there are oiliness improvers such as long-chain fatty acid esters and fatty amides, antifriction agents such as phosphate esters and zinc dithiophosphates, extreme pressure agents such as organic sulfur compounds and organic halogen compounds, friction modifiers such as organic molybdenum compounds, etc., but there is a problem that the antifriction effect is insufficient when only these additives are used depending on the conditions of use and the use environment. In order to overcome this problem, research on the use of polymer materials as antifriction agents has been conducted.
[0005] For example, Patent Document 1 discloses that a (meth)acrylic acid-based graft copolymer can be preferably used as a friction modifier.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2022-113676 Summary of the invention
[0009] However, the friction reduction effect is not sufficient in the method of Patent Document 1. In addition, since the viscosity of the lubricating oil composition is high, the energy loss due to stirring resistance increases, and thus the fuel saving performance deteriorates.
[0010] An object of the present invention is to provide a polymer, and to provide a polymer lubricating oil additive, a friction reducing agent for lubricating oil, and a lubricating oil composition having a high friction reducing effect and low viscosity by using the polymer.
[0011] The present invention has the following aspects.
[0012] [1] A polymer having a main chain polymer structure and a side chain polymer structure,
[0013] The side chain polymer structure comprises a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms,
[0014] The mass average molecular weight is 90,000 or less.
[0015] [2] The polymer according to claim 1, wherein a base oil solution containing 2% by mass of the polymer is prepared, and the kinematic viscosity at 40°C measured in accordance with the ASTM D7279 (D445) method is 22.4 cSt or less,
[0016] The above base oil is API standard Group III+.
[0017] [3] A polymer having a main chain polymer structure and a side chain polymer structure,
[0018] The side chain polymer structure comprises a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms,
[0019] A base oil solution containing 2% by mass of the above polymer is prepared, and the kinematic viscosity at 40° C. measured according to the ASTM D7279 (D445) method is 22.4 cSt or less.
[0020] The above base oil is API standard Group III+.
[0021] [4] The polymer according to [3], wherein the mass average molecular weight is less than 50,000.
[0022] [5] The polymer according to any one of [1] to [4], further comprising a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms.
[0023] [6] The polymer according to any one of [1] to [5], comprising a structural unit derived from a vinyl radical polymerizable monomer (m1).
[0024] [7] The polymer according to any one of [1] to [6], wherein the ratio of the main chain polymer structure is preferably 5 to 98% by mass, more preferably 10 to 95% by mass, and even more preferably 20 to 90% by mass, relative to the total mass of the polymer.
[0025] [8] The polymer according to any one of [1] to [7], wherein the ratio of the side chain polymer structure is preferably 2 to 95% by mass, more preferably 5 to 90% by mass, and even more preferably 10 to 80% by mass, relative to the total mass of the polymer.
[0026] [9] The copolymer according to any one of [1] to [8], wherein the alkyl (meth)acrylate (a) is preferably an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms, more preferably an alkyl (meth)acrylate having an alkyl group with 11 to 18 carbon atoms, and still more preferably an alkyl (meth)acrylate having an alkyl group with 11 to 14 carbon atoms.
[0027]
[10] The polymer according to any one of [1] to [9], wherein the content of the structural unit derived from the (meth)acrylate (a) is preferably 50 to 100% by mass, more preferably 60 to 100% by mass, further preferably 70 to 99% by mass, and particularly preferably 80 to 98% by mass, relative to the total mass of the side chain polymer structure.
[0028]
[11] The polymer according to any one of [1] to
[10] , wherein the content of the structural unit derived from the (meth)acrylate (a) is preferably 20 to 98% by mass, more preferably 25 to 95% by mass, and even more preferably 30 to 90% by mass, relative to the total mass of the polymer.
[0029]
[12] The polymer according to any one of [1] to
[11] , further comprising a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms, wherein the (meth)acrylate (b) is preferably a (meth)acrylate having a linear or branched alkyl group, more preferably an alkyl acrylate having an alkyl group with 2 to 8 carbon atoms, further preferably an alkyl acrylate having an alkyl group with 2 to 4 carbon atoms, and particularly preferably n-butyl acrylate.
[0030]
[13] The copolymer according to any one of [1] to
[12] , further comprising a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms, wherein the content of the structural unit derived from the (meth)acrylate (b) is preferably 3 to 80% by mass, more preferably 5 to 75% by mass, and even more preferably 10 to 70% by mass, relative to the total mass of the polymer.
[0031]
[14] The copolymer according to any one of [1] to
[13] , further comprising a structural unit derived from another free radical polymerizable vinyl compound (c) which is not any of the structural units derived from the above-mentioned alkyl (meth)acrylate (a) and the structural units derived from the alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms, wherein the above-mentioned free radical polymerizable vinyl compound (c) is preferably an alkyl (meth)acrylate having a polar group, more preferably an alkyl (meth)acrylate having a hydroxyl group, a carboxyl group, an amino group or an amide group, and even more preferably an alkyl (meth)acrylate having a hydroxyl group.
[0032]
[15] The copolymer according to any one of [1] to
[14] , further comprising a structural unit derived from another free radical polymerizable vinyl compound (c) which is not any of the structural units derived from the above-mentioned alkyl (meth)acrylate (a) and the structural units derived from the alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms, wherein the content of the structural unit derived from the above-mentioned other free radical polymerizable vinyl compound (c) is preferably 0 to 20% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, relative to the total mass of the polymer.
[0033]
[16] The polymer according to any one of [1] to
[15] , comprising a structural unit derived from a macromonomer (M).
[0034]
[17] The polymer according to
[16] , wherein the macromonomer (M) comprises a structural unit derived from the alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms.
[0035]
[18] The polymer according to
[16] , wherein the macromonomer (M) has a structure represented by the following formula (1).
[0036]
[0037] (Where X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH, Y 1 ~Y n Each independently represents a vinyl group bonded to the vinyl radical polymerizable monomer (m2) as the monomer structural unit of the macromonomer (M), excluding X 1 ~X n-1 Z represents a terminal group, and n represents an integer from 2 to 10000.
[0038]
[19] The polymer according to
[18] , wherein the vinyl radical polymerizable monomer (m2) contains the (meth)acrylic acid alkyl ester (a).
[0039]
[20] A polymer according to any one of
[16] to
[19] , wherein the content of the structural unit derived from the (meth)acrylate (a) is preferably 50 to 100% by mass, more preferably 60 to 100% by mass, further preferably 70 to 99% by mass, and particularly preferably 80 to 98% by mass, relative to the total mass of the macromonomer (M).
[0040]
[21] A polymer according to any one of
[16] to
[20] , wherein the macromonomer (M) contains a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms, and the content of the structural unit derived from the (meth)acrylate (b) is preferably 0.5 to 40% by mass, more preferably 1 to 30% by mass, and particularly preferably 1.5 to 20% by mass, relative to the total mass of the macromonomer (M).
[0041]
[22] A polymer according to any one of [1] to
[21] , wherein the ratio represented by [the content of structural units derived from the (meth)acrylic acid alkyl ester (b) having an alkyl group with 1 to 10 carbon atoms] / [the content of structural units derived from the (meth)acrylic acid alkyl ester (a)] in the macromonomer (M) is preferably 0.001 to 0.1, more preferably 0.005 to 0.05, and even more preferably 0.01 to 0.03.
[0042]
[23] A polymer according to any one of
[16] to
[22] , wherein the content of the structural unit derived from the macromonomer (M) is preferably 1 to 70% by mass, more preferably 2 to 60% by mass, and even more preferably 5 to 50% by mass, relative to the total mass of the polymer.
[0043]
[24] The polymer according to any one of
[16] to
[23] , wherein the mass average molecular weight (Mw) of the macromonomer (M) measured by gel permeation chromatography is preferably 5,000 to 50,000, more preferably 8,000 to 40,000, and even more preferably 10,000 to 30,000.
[0044]
[25] The polymer according to any one of
[16] to
[24] , wherein the number average molecular weight (Mn) of the macromonomer (M) measured by gel permeation chromatography (GPC) is preferably 500 to 30,000, more preferably 1,000 to 25,000, and particularly preferably 2,000 to 20,000.
[0045]
[26] The polymer according to any one of
[16] to
[25] , wherein the molecular weight distribution (Mw / Mn) of the macromonomer (M) measured by gel permeation chromatography is preferably 1.0 to 10, more preferably 1.2 to 8, and even more preferably 1.5 to 5.
[0046]
[27] The polymer according to any one of [1] to
[26] , wherein the mass average molecular weight (Mw) of the polymer measured by GPC is preferably 90,000 or less, more preferably 10,000 to 90,000, further preferably 12,000 to 85,000, particularly preferably 15,000 to 80,000, and most preferably 20,000 to 75,000.
[0047]
[28] The polymer according to any one of [1] to
[27] , wherein the number average molecular weight (Mn) of the polymer measured by gel permeation chromatography (GPC) is preferably 5,000 to 50,000, more preferably 7,000 to 40,000, and even more preferably 10,000 to 30,000.
[0048]
[29] The polymer according to any one of [1] to
[28] , wherein the molecular weight distribution (Mw / Mn) of the polymer measured by gel permeation chromatography (GPC) is preferably 1.0 to 20, more preferably 1.5 to 15, and even more preferably 2.0 to 10.
[0049]
[30] A polymer according to any one of [1] to
[29] , wherein a base oil solution containing 2% by mass of the polymer is prepared, and the friction coefficient measured at 40°C using an SRV5 tester (manufactured by Optimol Instruments Pruftechnik GmbH) is preferably 0.16 or less, more preferably less than 0.138, and even more preferably 0.135 or less.
[0050]
[31] The polymer according to any one of [1] to
[30] , wherein a base oil solution containing 2% by mass of the polymer is prepared, and the kinematic viscosity at 40°C measured according to ASTM D7279 (D445) is preferably 0 to 22.4 cSt, more preferably 5 cSt or more and less than 22.25 cSt, further preferably 10 cSt to 22.00 cSt, and particularly preferably 15 to 21.50 cSt.
[0051] The above base oil is API standard Group III+.
[0052]
[32] A lubricating oil additive comprising the polymer described in any one of [1] to
[31] .
[0053]
[33] A friction reducer for lubricating oil, comprising the polymer according to any one of [1] to
[31] and a base oil.
[0054]
[34] The friction reducer for lubricating oil according to
[33] , wherein the base oil is a base oil of API Group III, a base oil of API Group III+, or a base oil of API Group IV.
[0055]
[35] The friction reducer for lubricating oil according to
[33] or
[34] , wherein the content of the above-mentioned polymer is preferably 10 to 80 mass %, more preferably 15 to 70 mass %, and even more preferably 20 to 60 mass %, when the total mass of the lubricating oil additive is set to 100 mass %.
[0056]
[36] A lubricating oil composition comprising the friction reducing agent for lubricating oil according to any one of
[33] to
[35] .
[0057]
[37] The lubricating oil composition according to
[36] , wherein the content of the polymer is preferably 0.01 to 30 mass %, more preferably 0.05 to 25 mass %, and even more preferably 0.1 to 20 mass %, when the total mass of the lubricating oil composition is 100 mass %.
[0058]
[38] A use of the polymer described in any one of [1] to
[31] for producing a lubricating oil composition.
[0059]
[39] A use of the polymer described in any one of [1] to
[31] for reducing friction.
[0060]
[40] A use of the polymer described in any one of [1] to
[31] for improving lubricity.
[0061]
[41] A use of a composition comprising the polymer described in any one of [1] to
[31] for reducing friction.
[0062]
[42] A use of a composition comprising the polymer according to any one of [1] to
[31] for improving lubricity.
[0063]
[43] The use according to
[41] or
[42] , wherein the composition contains a solvent.
[0064]
[44] The use according to
[43] , wherein the solvent is a base oil.
[0065]
[45] The use according to
[44] , wherein the base oil is a base oil of API standard Group III, a base oil of API standard Group III+, or a base oil of API standard Group IV.
[0066]
[46] The use according to any one of
[41] to
[45] , wherein the content of the above-mentioned polymer is preferably 0.01 to 30 mass %, more preferably 0.05 to 25 mass %, and even more preferably 0.1 to 20 mass %, when the total mass of the composition is set to 100 mass %.
[0067] Furthermore, the present invention has the following aspects.
[0068] [1] A friction reducer for lubricating oil, comprising a (meth)acrylic acid graft copolymer A having a main chain polymer structure and a side chain polymer structure,
[0069] The (meth)acrylic graft copolymer A contains a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms in the side chain polymer structure, and has a mass average molecular weight of 10,000 to 90,000.
[0070] [2] The friction reducer for lubricating oil according to [1], wherein the (meth)acrylic graft copolymer A further comprises a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 1 to 10 carbon atoms (b).
[0071] [3] The friction reducer for lubricating oil according to [1], wherein the (meth)acrylic graft copolymer A comprises a structural unit derived from a vinyl radical polymerizable monomer (m1) and a structural unit derived from a macromonomer (M).
[0072] [4] The friction reducer for lubricating oil according to [3], wherein the macromonomer (M) comprises a structural unit derived from the alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms.
[0073] [5] The friction reducer for lubricating oil according to [3], wherein the macromonomer (M) has a structure represented by the following formula (1).
[0074]
[0075] (Where X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH, Y 1 ~Y n Each independently represents a vinyl group bonded to the vinyl radical polymerizable monomer (m2) as the monomer structural unit of the macromonomer (M), excluding X1 ~X n-1 Z represents a terminal group, and n represents an integer from 2 to 10000.
[0076] [6] A lubricating oil composition comprising the friction reducing agent for lubricating oil according to any one of [1] to [5].
[0077] According to the polymer of the present invention, it is possible to provide a polymer lubricating oil additive, a friction reducing agent for lubricating oil, and a polymer lubricating oil composition having a high friction reducing effect and low viscosity. DETAILED DESCRIPTION
[0078] The present invention will be described in detail below. The following embodiments are merely examples for describing the present invention, and are not intended to limit the present invention to these embodiments. The present invention can be implemented in various ways without departing from the gist thereof.
[0079] It should be noted that in the present invention, "(meth)acrylic acid" is a general term for "acrylic acid" and "methacrylic acid". "(Meth)acrylate" is a general term for "acrylate" and "methacrylate". "(Meth)acryloyl" is a general term for "acryloyl" and "methacryloyl", and is a group represented by CH2=C(R)-C(=O)- (R is a hydrogen atom or a methyl group). "Macromer" refers to a polymer having a free radical polymerizable group or an addition reactive functional group. "Vinyl-based free radical polymerizable monomer" refers to a monomer having an ethylenically unsaturated bond that is not a macromonomer.
[0080] The polymer in the first aspect of the present invention has a main chain polymer structure and a side chain polymer structure, wherein the side chain polymer structure includes a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms and has a mass average molecular weight of 90,000 or less.
[0081] The polymer in the second embodiment of the present invention has a main chain polymer structure and a side chain polymer structure, the side chain polymer structure contains a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms, and a base oil solution containing 2% by mass of the polymer is prepared, and the kinematic viscosity at 40° C. measured according to the ASTM D7279 (D445) method is 22.4 cSt or less, and the base oil is API standard Group III+.
[0082] The polymer is preferably a graft copolymer in which at least a part of the structural units are structural units derived from a (meth)acrylic monomer. The polymer may further include structural units derived from a monomer other than the (meth)acrylic monomer (for example, styrene, etc.).
[0083] The polymer is preferably a graft copolymer consisting of a main chain polymer structure and a side chain polymer structure (branched polymer structure) chemically bonded to the main chain polymer structure (trunk polymer structure). In this specification, a graft copolymer refers to a polymer having one or more blocks connected to the main chain polymer structure as a side chain polymer structure. The structures of the main chain polymer and the side chain polymer may be different or the same. There are no particular limitations on the method for producing the graft copolymer, and examples include: a method in which a macromolecular monomer having a free radical polymerizable double bond at the end is manufactured into a side chain polymer structure and then subjected to free radical polymerization with a monomer as a structural unit of the main chain polymer, a method in which a main chain polymer having a reaction site and a macromolecular monomer having a reaction site are pre-manufactured and then reacted, a method in which an initiator having hydrogen abstraction ability is used after the manufacture of the main chain polymer to generate free radicals on the main chain polymer and reacted with a monomer as a structural unit of the side chain polymer to produce a side chain polymer structure, etc.
[0084] The polymer preferably contains a structural unit derived from an alkyl (meth)acrylate having 11 to 30 carbon atoms in the alkyl group (a) (hereinafter also referred to as "component (a)") in the side chain polymer structure, and has a mass average molecular weight of 10,000 to 90,000. It may further contain a structural unit derived from an alkyl (meth)acrylate having 1 to 10 carbon atoms in the alkyl group (b) (hereinafter also referred to as "component (b)")
[0085] The total amount of the components (a) and (b) as structural units is preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass, based on the total mass of the polymer.
[0086] The polymer may contain a structural unit derived from the component (a) in the side chain polymer structure. The polymer may contain a structural unit derived from the component (a) in both the side chain polymer structure and the main chain polymer structure.
[0087] As the above-mentioned (a) component, for example, n-undecyl (meth)acrylate, iso-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, iso-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, iso-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, iso-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, iso-hexadecyl (meth)acrylate, n-stearyl (meth)acrylate, isostearyl (meth)acrylate, n-octadecyl (meth)acrylate, iso-octadecyl (meth)acrylate, n-behenyl (meth)acrylate, iso-behenyl (meth)acrylate, etc. These may be used in combination of two or more.
[0088] From the viewpoint of being able to reduce the viscosity of the lubricating oil composition, the component (a) is preferably an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms, more preferably an alkyl (meth)acrylate having an alkyl group with 11 to 18 carbon atoms, and still more preferably an alkyl (meth)acrylate having an alkyl group with 11 to 14 carbon atoms.
[0089] From the viewpoint of being able to improve the solubility of the polymer in the base oil, the component (a) is preferably an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms, more preferably an alkyl methacrylate having an alkyl group with 11 to 20 carbon atoms, further preferably an alkyl methacrylate having an alkyl group with 11 to 18 carbon atoms, and particularly preferably an alkyl methacrylate having an alkyl group with 11 to 14 carbon atoms.
[0090] From the viewpoint of improving the friction reduction effect and lowering the viscosity of the lubricating oil composition, the content of the structural units derived from the component (a) is preferably 20 to 98% by mass, more preferably 25 to 95% by mass, and even more preferably 30 to 90% by mass, based on the total mass of the polymer.
[0091] As the component (b), for example, there can be mentioned alkyl (meth)acrylates having a linear alkyl group such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and n-nonyl (meth)acrylate; alkyl (meth)acrylates having a branched alkyl group such as isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; and alkyl (meth)acrylates having a cyclic alkyl group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, isobornyl (meth)acrylate, and 4-tert-butylcyclohexyl (meth)acrylate. Two or more of these may be used in combination.
[0092] From the viewpoint of improving the friction-reducing effect, the component (b) is preferably a (meth)acrylate having a linear or branched alkyl group, more preferably an alkyl acrylate having an alkyl group with 2 to 8 carbon atoms, further preferably an alkyl acrylate having an alkyl group with 2 to 4 carbon atoms, and particularly preferably n-butyl acrylate.
[0093] From the viewpoint of improving the friction reduction effect and lowering the viscosity of the lubricating oil composition, the content of the structural unit derived from the component (b) is preferably 3 to 80 mass %, more preferably 5 to 75 mass %, and even more preferably 10 to 70 mass %, based on the total mass of the polymer.
[0094] Since the solubility of the above-mentioned polymer in the base oil can be improved, the above-mentioned polymer preferably contains the above-mentioned structural unit derived from the (a) component as a structural unit in the side chain polymer structure, and more preferably contains the above-mentioned structural unit derived from the (a) component as a structural unit in both the side chain polymer structure and the main chain polymer structure.
[0095] The polymer preferably contains the structural unit derived from the component (b) as a structural unit in the side chain polymer structure, and more preferably contains the structural unit derived from the component (b) as a structural unit in both the side chain polymer structure and the main chain polymer structure.
[0096] The mass average molecular weight (Mw) of the polymer is preferably 90,000 or less. From the perspective of being able to reduce the viscosity of the lubricating oil composition, the mass average molecular weight of the polymer is more preferably 10,000 to 90,000, further preferably 12,000 to 85,000, particularly preferably 15,000 to 80,000, and most preferably 20,000 to 75,000.
[0097] The polymer may contain structural units derived from other radical polymerizable vinyl compounds (hereinafter also referred to as "(c) component") other than components (a) and (b). Examples of other radical polymerizable vinyl compounds include styrene, α-methylstyrene, p-tert-butylstyrene, vinyltoluene, vinyl acetate, and (meth)acrylate compounds other than components (a) and (b).
[0098] Examples of the (meth)acrylate compound other than the components (a) and (b) include alkyl (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerol mono(meth)acrylate, ethylene glycol mono(meth)acrylate, and propylene glycol mono(meth)acrylate; and alkyl (meth)acrylates having a hydroxyl group, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate; and (Meth)acrylic acid alkyl esters containing a carboxyl group, such as (meth)acryloxyethyl ethyl, 2-(meth)acryloxyethyl maleate, 2-(meth)acryloxyethyl phthalate, and 2-(meth)acryloxyethyl hexahydrophthalate; (meth)acrylic acid phenyl ester, (meth)acrylic acid benzyl ester, (meth)acrylic acid phenoxyethyl ester, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxy Alkyl (meth)acrylates having an aromatic ring structure such as propylene glycol (meth)acrylate, phenyl phenyl (meth)acrylate, phenyl phenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenyl benzyl (meth)acrylate, naphthyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate; Alkyl (meth)acrylates having a heterocyclic structure such as tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, and (meth)acryloylmorpholine; Alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and butoxyethyl (meth)acrylate; 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, (meth)acrylamide, and the like. These may be used in combination of two or more.
[0099] From the viewpoint of improving the friction reduction effect and lowering the viscosity of the lubricating oil composition, the content of the structural unit derived from the component (c) is preferably 0 to 20% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, based on the total mass of the polymer.
[0100] The total amount of the structural units derived from the components (a) to (c) is not more than 100% by mass based on the total mass of the polymer.
[0101] The polymer may include a structural unit derived from a vinyl radical polymerizable monomer (m1) (hereinafter also referred to as “component (m1)”) and a structural unit derived from a macromonomer (M) (hereinafter also referred to as “component (M)”).
[0102] Examples of the component (m1) include styrene, vinyl acetate, and (meth)acrylate compounds. Examples of the (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, and n-hexadecyl (meth)acrylate. (meth)acrylate alkyl esters having a straight-chain alkyl group, such as (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, isopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, 3-isopropylheptyl (meth)acrylate, isoundecyl (meth)acrylate, 2-tert-butylheptyl (meth)acrylate, isododecyl (meth)acrylate Alkyl (meth)acrylates having a branched alkyl group, such as alkyl (meth)acrylate, isotridecyl (meth)acrylate, isotetradecyl (meth)acrylate, and isodocosyl (meth)acrylate; Alkyl (meth)acrylates having a cyclic alkyl group, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and adamantyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, Alkyl (meth)acrylates having a hydroxyl group, such as ester, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerol mono(meth)acrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate; Alkyl (meth)acrylates containing a carboxyl group, such as (meth)acrylic acid, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxyethyl hexahydrophthalate;Alkyl (meth)acrylates having an aromatic ring structure such as phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate; alkyl (meth)acrylates having a heterocyclic structure such as tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, and (meth)acryloylmorpholine Alkyl (meth)acrylates with a ring structure; alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and butoxyethyl (meth)acrylate; allyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and (meth)acrylamide. Two or more of these may be used in combination. ;
[0103] From the viewpoint of improving the friction reduction effect, the component (m1) preferably contains the component (b), more preferably an alkyl acrylate having an alkyl group with 2 to 8 carbon atoms, further preferably an alkyl acrylate having an alkyl group with 2 to 4 carbon atoms, and particularly preferably n-butyl acrylate.
[0104] From the viewpoint of being able to improve the solubility of the polymer in the base oil, the component (m1) preferably contains the component (a), more preferably an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms, further preferably an alkyl (meth)acrylate having an alkyl group with 11 to 18 carbon atoms, and particularly preferably an alkyl (meth)acrylate having an alkyl group with 11 to 14 carbon atoms.
[0105] The above-mentioned (M) component is a compound containing two or more structural units derived from a monomer (m2) having a vinyl radical polymerizable group (hereinafter, also referred to as "(m2) component") and having a radical polymerizable group at the end, and contains the above-mentioned (a) component as the (m2) component. As the (m2) component other than the (a) component, the compounds mentioned as the above-mentioned (m1) component can be mentioned. From the aspect of being able to improve the solubility of the polymer in the base oil, as the (m2) component, preferably, an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms, more preferably, an alkyl methacrylate having an alkyl group with 11 to 20 carbon atoms, further preferably, an alkyl methacrylate having an alkyl group with 11 to 18 carbon atoms, and particularly preferably, an alkyl methacrylate having an alkyl group with 11 to 14 carbon atoms. In addition, it is preferred to contain the above-mentioned (b) component as the (m2) component. From the perspective of being able to improve the solubility of the polymer in the base oil, the component (m2) is preferably a (meth)acrylate having a linear or branched alkyl group, more preferably an alkyl methacrylate having an alkyl group with 1 to 8 carbon atoms, further preferably an alkyl methacrylate having an alkyl group with 1 to 4 carbon atoms, and particularly preferably methyl methacrylate.
[0106] From the perspective of being able to improve the solubility of the polymer in the base oil, the structural units derived from the component (a) are preferably contained in an amount of 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 80% by mass or more, relative to the total mass of the component (M).
[0107] Furthermore, from the viewpoint of radical polymerizability, the component (M) preferably has a structure represented by the following formula (1).
[0108]
[0109] (Where X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH, Y 1 ~Y n Each independently represents a vinyl group bonded to the (m2) component as the monomer structural unit of the macromonomer (M), excluding X 1 ~X n-1 Z represents a terminal group, and n represents an integer from 2 to 10000.
[0110] X 1 ~X n-1 and Y 1 ~Y n Each is independently a substituent bonded to the vinyl group of the component (m2). 1 ~Y nFor example, to express OR 1 , halogen atoms, COR 2 、COOR 3 、CN、CONR 4 R 5 、NHCOR 6 , or R 7 , R 1 ~R 7 Each independently represents a hydrogen atom, an alkyl group, an aryl group, a heteroaryl group or the like.
[0111] In addition, Z as the terminal group is the same as the terminal group of a polymer obtained by known radical polymerization, and examples thereof include a hydrogen atom and a group derived from a radical polymerization initiator.
[0112] In addition, from the viewpoint of improving the solubility of the polymer in the base oil and improving the friction reducing effect, the content of the structural unit derived from the component (M) is preferably 1 to 70 mass %, more preferably 2 to 60 mass %, and even more preferably 5 to 50 mass % relative to the total mass of the polymer.
[0113] The polymer preferably contains two or more structural units derived from the component (M).
[0114] From the perspective of being able to improve the solubility of the polymer in the base oil, the content of the structural units derived from the component (b) is preferably greater than 0 mass % and less than 50 mass %, more preferably 0.5 to 40 mass %, further preferably 1 to 30 mass %, and particularly preferably 1.5 to 20 mass %, relative to the total mass of the component (M).
[0115] From the perspective of being able to improve the solubility of the polymer in the base oil, the ratio represented by [the content of the structural units derived from the component (b)] / [the content of the structural units derived from the component (a)] in the component (M) is preferably 0.001 to 0.1, more preferably 0.005 to 0.05, and even more preferably 0.01 to 0.03.
[0116] From the perspective of improving the solubility of the polymer in the base oil and improving the friction-reducing effect, the mass average molecular weight (Mw) of the macromonomer (M) measured by gel permeation chromatography (GPC) is preferably 5,000 to 50,000, more preferably 8,000 to 40,000, and even more preferably 10,000 to 30,000.
[0117] The number average molecular weight (Mn) of the component (M) as measured by gel permeation chromatography is preferably 500 to 30,000, more preferably 1,000 to 25,000, and particularly preferably 2,000 to 20,000, from the viewpoint of improving the solubility of the polymer in the base oil and improving the friction reducing effect.
[0118] The molecular weight distribution (Mw / Mn) of the macromonomer (M) as measured by gel permeation chromatography (GPC) is preferably 1.0 to 10, more preferably 1.2 to 8, and even more preferably 1.5 to 5, from the viewpoint of improving the solubility of the polymer in the base oil and improving the friction reducing effect.
[0119] The above-mentioned (M) component may be a compound produced by a known method or a commercially available compound. As a method for producing the above-mentioned M component, for example, a method using a cobalt chain transfer agent (U.S. Patent No. 4,680,352), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (International Publication No. 88 / 04304), a method of chemically bonding a polymerizable group (Japanese Patent Publication No. 60-133007 and U.S. Patent No. 5,147,952), and a method based on thermal decomposition (Japanese Patent Publication No. 11-240854).
[0120] The method of using a cobalt chain transfer agent is preferred in terms of fewer production steps and the use of a catalyst with a high chain transfer constant. Since a cobalt chain transfer agent has a high chain transfer constant, a macromonomer with a controllable molecular weight can be obtained by adding a small amount of the cobalt chain transfer agent.
[0121] As the cobalt chain transfer agent, a known cobalt complex can be used. The amount of the cobalt chain transfer agent is preferably 0.00001 to 0.1 parts by mass, more preferably 0.00005 to 0.05 parts by mass, and particularly preferably 0.0001 to 0.02 parts by mass, based on 100 parts by mass of the component (m2).
[0122] In addition, from the perspective of improving the solubility of the polymer in the base oil and improving the friction reducing effect, the number average molecular weight (Mn) of the polymer contained in the friction reducing agent for lubricating oil of the present invention measured by gel permeation chromatography (GPC) is preferably 5,000 to 50,000, more preferably 7,000 to 40,000, and even more preferably 10,000 to 30,000.
[0123] In addition, from the perspective of improving the solubility of the polymer in the base oil and improving the friction reducing effect, the molecular weight distribution (Mw / Mn) of the polymer contained in the friction reducing agent for lubricating oil of the present invention measured by gel permeation chromatography (GPC) is preferably 1.0 to 20, more preferably 1.5 to 15, and even more preferably 2.0 to 10.
[0124] An example of a method for producing the friction reducing agent for lubricating oil of the present invention is shown below.
[0125] The friction reducing agent for lubricating oil of the present invention can be produced by polymerizing a monomer mixture containing the above-mentioned component (m1) and the above-mentioned component (M) in a base oil by a known method.
[0126] The base oil is not particularly limited, and examples thereof include API Group III base oils such as Yubase 3 manufactured by SK Lubricant, API Group III+ base oils such as Yubase 4 manufactured by SK Lubricant, and API Group IV base oils such as poly-α-olefins.
[0127] In addition, the component (M) is preferably a macromonomer prepared by polymerizing a monomer mixture containing a vinyl radical polymerizable monomer in the base oil using a cobalt chain transfer agent. Since the cobalt chain transfer agent has a high chain transfer constant, a macromonomer with controllable molecular weight can be obtained by adding a small amount of the cobalt chain transfer agent.
[0128] The polymerization may be carried out under known conditions, and it is preferred to use α-methylstyrene dimer as a chain transfer agent because of its particularly excellent effect of suppressing heat generation during polymerization.
[0129] The friction reducer for lubricating oil containing the polymer of the present invention can be used in mobile devices such as automobiles and ships, industrial machinery, robots, etc., and can be used as a friction reducer for lubricating oil added to lubricating oils such as engine oil, drive system oil (gear oil, transmission oil), hydraulic oil, metalworking oil, etc.
[0130] Examples of the base oil of the lubricating oil include mineral base oils purified from crude oil and chemically synthesized synthetic oils. For example, examples include API standard Group III base oils such as YUBASE 3 manufactured by SK Lubricant, API standard Group III+ base oils such as YUBASE 4 manufactured by SK Lubricant, and API standard Group IV base oils such as polyalphaolefins.
[0131] The lubricating oil composition of the present invention contains the lubricating oil friction reducer of the present invention. The lubricating oil composition of the present invention may also contain other additives in addition to the lubricating oil friction reducer of the present invention. As other additives, antioxidants, viscosity index improvers, pour point depressants, detergent dispersants, preservatives, rust inhibitors, defoamers, emulsifiers, mildew inhibitors, anti-emulsifiers, etc. can be cited. In addition, as friction reducers other than the present invention, oiliness improvers such as long-chain fatty acid esters and fatty amides, anti-wear agents such as phosphate esters and zinc dithiophosphates, extreme pressure agents such as organic sulfur compounds and organic halogen compounds, friction modifiers such as organic molybdenum compounds, etc. can be contained.
[0132] The lubricating oil composition of the present invention may also be a grease containing a thickener. Examples of the thickener include soap-based (lithium soap, calcium soap, sodium soap, aluminum soap, etc.), inorganic-based (bentonite, silica gel, etc.), and organic-based (polyurea, polyurethane, etc.).
[0133] The content of the polymer of the present invention contained in the lubricating oil composition is preferably 0.01 to 30% by mass, more preferably 0.05 to 25% by mass, and even more preferably 0.1 to 20% by mass, relative to 100% by mass of the lubricating oil composition. The friction reducing effect can be improved by setting the content of the friction reducing agent for lubricating oil to 0.01% by mass or more. The viscosity of the lubricating oil composition can be reduced by setting the content to 30% by mass or less.
[0134] A base oil solution containing 2 mass % of the polymer is prepared, and the friction coefficient measured at 40° C. using an SRV5 tester (manufactured by Optimol Instruments Pruftechnik GmbH) is preferably 0.16 or less, more preferably less than 0.138, and even more preferably 0.135 or less.
[0135] A base oil solution containing 2% by mass of the polymer is prepared, and the kinematic viscosity at 40°C measured according to ASTM D7279 (D445) is preferably 0 to 22.4 cSt, more preferably 5 to 22.25 cSt, further preferably 10 to 22.00 cSt, particularly preferably 15 to 21.50 cSt.
[0136] It should be noted that the above base oil is API standard Group III+.
[0137] Example
[0138] Hereinafter, the present invention will be described in more detail based on examples and comparative examples. It should be noted that "parts" in the examples represent "parts by mass". Evaluation was performed according to the following method. In addition, in Tables 1 to 6, the content of the structural unit from each monomer is expressed in mass %. The content of each structural unit is calculated from the mass of the monomer relative to the total mass of the monomer used in the polymerization reaction.
[0139] <Molecular weight of macromonomer (M)>
[0140] The measurement was performed using a gel permeation chromatography (GPC) (HLC-8320 manufactured by Tosoh Corporation). After preparing a 0.2 mass % tetrahydrofuran solution of the macromonomer (M), 10 μl of the solution was injected into a device equipped with a chromatographic column manufactured by Tosoh Corporation (TSKgel SuperHZM-M (inner diameter 4.6 mm, length 15 cm), HZM-M (inner diameter 4.6 mm, length 15 cm), HZ-2000 (inner diameter 4.6 mm, length 15 cm), TSKguardcolumn SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm), and the measurement was performed under the conditions of flow rate: 0.35 ml / min, eluent: tetrahydrofuran (stabilizer BHT), column temperature: 40°C, and Mw, Mn, and Mw / Mn were calculated by conversion to standard polystyrene.
[0141] <Molecular weight of polymer>
[0142] The measurement was performed using gel permeation chromatography (GPC) (HLC-8320 manufactured by Tosoh Corporation). After preparing a 0.2% by mass tetrahydrofuran solution of the polymer obtained in the example, 10 μl of the above solution was injected into a device equipped with a chromatographic column manufactured by Tosoh Corporation (2 TSKgelSuperHZM-H (inner diameter 6.0 mm, length 15 cm), TSKguardcolumn SuperHZ-H (inner diameter 4.6 mm, length 3.5 cm), and the measurement was performed under the conditions of a flow rate of 0.5 ml / min, eluent: tetrahydrofuran (stabilizer BHT), and column temperature: 40°C. The mass average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) were calculated by conversion to standard polystyrene.
[0143] <Kinematic viscosity at 40℃>
[0144] A YUBASE 4 solution containing 2% by mass of the obtained polymer was prepared, and the kinematic viscosity at 40° C. was evaluated using a fully automatic simple kinematic viscometer (manufactured by Cannon, trade name: Simple-VIS) in accordance with ASTM D7279 (D445).
[0145] <Friction coefficient at 40℃>
[0146] A YUBASE4 solution containing 2% by mass of the obtained polymer was prepared, and the friction coefficient was measured at 40° C. using an SRV5 tester (manufactured by Optimol Instruments Pruftechnik GmbH). The measurement conditions were as follows, and the friction coefficient was evaluated 60 minutes after the start of the measurement.
[0147] ·Test method: Ball-on-disk method (ball diameter: 10 mm, material of ball and disk: SUJ2)
[0148] Test mode: reciprocating (50Hz, stroke 1mm)
[0149] Load: 200N
[0150] [Production Example 1]
[0151] (Synthesis of Co complex (cobalt chain transfer agent))
[0152] In a synthesis apparatus equipped with a stirring device, 2.00 g (8.03 mmol) of cobalt (II) acetate tetrahydrate (Wako Pure Chemical Industries, Ltd., Wako Special Grade), 3.86 g (16.1 mmol) of diphenylglyoxime (Tokyo Chemical Industry Co., Ltd., EP Grade) and 100 ml of diethyl ether previously deoxygenated by nitrogen bubbling were charged under a nitrogen atmosphere and stirred at 25°C for 2 hours.
[0153] Next, 20 ml of boron trifluoride diethyl ether complex (manufactured by Tokyo Chemical Industry Co., Ltd., EP grade) was added and stirred for further 6 hours. The obtained reaction solution was filtered, and the solid was washed with diethyl ether and dried at 100 MPa or less and 20° C. for 12 hours to obtain 5.02 g (7.93 mmol, yield 99 mass %) of a dark brown solid Co complex.
[0154] [Production Example 2]
[0155] (Synthesis of Macromonomer M1)
[0156] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 58 parts of YUBASE4, 98 parts of Acrylic EsterSL (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester SL, a mixture of an alkyl methacrylate having 12 carbon atoms in the alkyl group and an alkyl methacrylate having 13 carbon atoms in the alkyl group), 2 parts of methyl methacrylate (MMA), and 0.005 parts of the Co complex prepared in Production Example 1 were added, and the liquid temperature was raised to 40°C, and nitrogen was bubbled for 2 hours while stirring to remove dissolved oxygen. A mixed solution consisting of 2 parts of YUBASE4 and 0.1 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by ARKEMA Yoshitomi, trade name: LUPEROX 26) as a polymerization initiator was added, and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixed solution consisting of 10 parts of YUBASE4 and 0.7 parts of LUPEROX 26 was added dropwise over 1 hour. After the dropwise addition, the temperature was raised to 105°C and maintained for 1.5 hours, then 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M1. The results of GPC of the obtained macromonomer M1 are shown in Table 1.
[0157] [Production Example 3]
[0158] (Synthesis of Macromonomer M2)
[0159] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 58 parts of YUBASE4, 98 parts of Acrylic EsterSL, 2 parts of MMA and 0.005 parts of the Co complex prepared in Preparation Example 1 were added, and the liquid temperature was raised to 40°C, and nitrogen was bubbled for 2 hours while stirring to remove dissolved oxygen. A mixed solution consisting of 0.1 parts of YUBASE4 (2 parts) and tert-amyl peroxy-2-ethylhexanoate (manufactured by ARKEMA Yoshitomi Co., Ltd., trade name: LUPEROX 575) as a polymerization initiator was added and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixed solution consisting of YUBASE4 (10 parts) and LUPEROX 26 (0.7 parts) was added dropwise over 1 hour. After the addition, the temperature was raised to 105°C and maintained for 1.5 hours, and then 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M2. Table 1 shows the results of GPC of the obtained macromonomer M2.
[0160] [Production Example 4]
[0161] (Synthesis of Macromonomer M3)
[0162] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 58 parts of YUBASE4, 98 parts of n-octadecyl methacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name: Light Ester S), 2 parts of methyl methacrylate (MMA), and 0.005 parts of the Co complex prepared in Preparation Example 1 were added, and the liquid temperature was raised to 40°C while stirring and nitrogen bubbling was performed for 2 hours to remove dissolved oxygen. A mixed solution consisting of YUBASE4 (2 parts) and LUPEROX 26 (0.2 parts) as a polymerization initiator was added and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixed solution consisting of YUBASE4 (10 parts) and LUPEROX 26 (0.7 parts) was added dropwise over 1 hour. After the addition, the temperature was raised to 105°C and maintained for 1.5 hours, and then 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M3. Table 1 shows the results of GPC of the obtained macromonomer M3.
[0163] [Production Example 5]
[0164] (Synthesis of Macromonomer M4)
[0165] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 58 parts of YUBASE4, 98 parts of lauryl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester L), 2 parts of methyl methacrylate (MMA), and 0.005 parts of the Co complex prepared in Preparation Example 1 were added, and the liquid temperature was raised to 40°C while stirring and nitrogen bubbling was performed for 2 hours to remove dissolved oxygen. A mixed solution consisting of YUBASE4 (2 parts) and LUPEROX 26 (0.4 parts) as a polymerization initiator was added and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixed solution consisting of YUBASE4 (10 parts) and LUPEROX 26 (0.7 parts) was added dropwise over 1 hour. After the addition, the temperature was raised to 105°C and maintained for 1.5 hours, and then 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M4. Table 1 shows the results of GPC of the obtained macromonomer M4.
[0166] [Production Example 6]
[0167] (Synthesis of Macromonomer M5)
[0168] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 58 parts of YUBASE4, 98 parts of Acrylic Ester SL, 2 parts of MMA and 0.0075 parts of the Co complex prepared in Preparation Example 1 were added, and the liquid temperature was raised to 40°C while stirring and nitrogen bubbling was performed for 2 hours to remove dissolved oxygen. A mixed solution consisting of 2 parts of YUBASE4 and 0.1 parts of tert-amyl peroxy-2-ethylhexanoate (manufactured by ARKEMA Yoshitomi Co., Ltd., trade name: LUPEROX 575) as a polymerization initiator was added and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixed solution consisting of 10 parts of YUBASE4 and 0.7 parts of LUPEROX 26 was added dropwise over 1 hour. After the addition, the temperature was raised to 105°C and maintained for 1.5 hours, and then 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M2. Table 1 shows the results of GPC of the obtained macromonomer M5.
[0169] [Production Example 7]
[0170] (Synthesis of Macromonomer M6)
[0171] 58 parts of YUBASE4, 100 parts of 2-ethylhexyl methacrylate, and 0.003 parts of the Co complex prepared in Preparation Example 1 were added to a reaction container equipped with a stirrer, a cooling tube, and a thermometer. The liquid temperature was raised to 40°C and nitrogen was bubbled for 2 hours while stirring to remove dissolved oxygen. A mixed solution consisting of 0.1 parts of YUBASE4 (2 parts) and tert-amyl peroxy-2-ethylhexanoate (manufactured by ARKEMA Yoshitomi Co., Ltd., trade name: LUPEROX 575) as a polymerization initiator was added and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixed solution consisting of YUBASE4 (10 parts) and LUPEROX 575 (0.7 parts) was added dropwise over 1 hour. After the addition, the temperature was raised to 105°C and maintained for 1.5 hours. Then, 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M6. Table 1 shows the results of GPC of the obtained macromonomer M6.
[0172] <Example 1>
[0173] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 2. In Tables 2 to 6, the polymer composition also includes the structural units in the macromonomer (M).
[0174] <Example 2>
[0175] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. Table 2 shows the evaluation results of the obtained friction reducing agent for lubricating oil.
[0176] <Example 3>
[0177] 30 parts of YUBASE4 and 9.5 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 71 parts of n-butyl acrylate, 24 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (56.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 2.
[0178] <Example 4>
[0179] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 40 parts of YUBASE4, 66.7 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3, 49 parts of n-butyl acrylate, 16 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.7 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and 42 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0180] <Example 5>
[0181] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 45 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0182] <Example 6>
[0183] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 30 parts of n-butyl acrylate, 45 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0184] <Example 7>
[0185] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 20 parts of n-butyl acrylate, 55 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0186] <Example 8>
[0187] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 30 parts of ethyl acrylate (manufactured by Mitsubishi Chemical Corporation), 45 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer (manufactured by NOF Corporation, trade name: NOFMER MSD) as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, maintained for 3.5 hours, and then a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0188] <Example 9>
[0189] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M3 obtained in Preparation Example 4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0190] <Example 10>
[0191] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M4 obtained in Preparation Example 5, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer (manufactured by NOF Corporation, trade name: NOFMER MSD) as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, maintained for 3.5 hours, and then a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0192] <Example 11>
[0193] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.2 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0194] <Example 12>
[0195] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of YUBASE4 (25 parts), n-butyl acrylate (50 parts), lauryl acrylate (25 parts), LUPEROX 575 (0.1 parts) as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. Table 3 shows the evaluation results of the obtained friction reducing agent for lubricating oil.
[0196] <Example 13>
[0197] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 20 parts of n-butyl acrylate, 25 parts of lauryl acrylate, 30 parts of n-butyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester B), 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. The temperature was raised to 110°C and maintained for 1 hour, and then YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0198] <Example 14>
[0199] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 20 parts of n-butyl acrylate, 25 parts of lauryl acrylate, 30 parts of AcrylicEster B, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining the temperature at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. Table 3 shows the evaluation results of the obtained friction reducing agent for lubricating oil.
[0200] <Example 15>
[0201] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 45 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0202] <Example 16>
[0203] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 60 parts of n-butyl acrylate, 15 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.2 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0204] <Example 17>
[0205] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 64 parts of n-butyl acrylate, 11 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.2 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0206] <Example 18>
[0207] 30 parts of YUBASE4 and 95.2 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 50 parts of n-butyl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and 1.2 parts of NOFMER MSD as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (35.4 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic acid graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0208] <Example 19>
[0209] 30 parts of YUBASE4 and 38.1 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 60 parts of n-butyl acrylate, 20 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (62.5 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0210] <Example 20>
[0211] 30 parts of YUBASE4 and 19 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 67 parts of n-butyl acrylate, 23 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (71.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 3.
[0212] <Example 21>
[0213] 50 parts of YUBASE4 and 9.5 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 71 parts of n-butyl acrylate, 24 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (56.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 4.
[0214] <Example 22>
[0215] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M5 obtained in Preparation Example 6 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.2 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 4.
[0216] <Example 23>
[0217] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M5 obtained in Preparation Example 6 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 45 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 4.
[0218] <Example 24>
[0219] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M5 obtained in Preparation Example 6 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 64 parts of n-butyl acrylate, 11 parts of lauryl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.2 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 4.
[0220] <Example 25>
[0221] 30 parts of YUBASE4 and 95.2 parts of the YUBASE4 solution of the macromonomer M5 obtained in Preparation Example 6 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 50 parts of n-butyl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.2 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (35.4 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 4.
[0222] <Example 26>
[0223] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3, 56 parts of 2-ethylhexyl acrylate (manufactured by Mitsubishi Chemical Corporation), 19 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 1.2 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0224] <Example 27>
[0225] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 1 part of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 4.
[0226] <Example 28>
[0227] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 18 parts of lauryl acrylate, 4-hydroxybutyl acrylate (Mitsubishi Chemical Corporation, trade name: 4HBA) (1 part), 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. The temperature was raised to 110°C and maintained for 1 hour, and then YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0228] <Example 29>
[0229] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 54 parts of n-butyl acrylate, 18 parts of lauryl acrylate, 4-hydroxybutyl acrylate (Mitsubishi Chemical Corporation, trade name: 4HBA) (3 parts), 3 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (4 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. The temperature was raised to 110°C and maintained for 1 hour, and then YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer.
[0230] <Example 30>
[0231] 30 parts of YUBASE4 and 95.2 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 50 parts of n-butyl acrylate, 1 part of LUPEROX 5751 as a polymerization initiator, and NOFMER MSD (1.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 5.
[0232] <Example 31>
[0233] 30 parts of YUBASE4 and 95.2 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 47 parts of n-butyl acrylate, 3 parts of 4-hydroxybutyl acrylate, 0.5 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. Table 5 shows the evaluation results of the obtained friction reducing agent for lubricating oil.
[0234] <Example 32>
[0235] 30 parts of YUBASE4 and 95.2 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 47 parts of n-butyl acrylate, 3 parts of 4-hydroxybutyl acrylate, 0.1 parts of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (1.3 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. Table 5 shows the evaluation results of the obtained friction reducing agent for lubricating oil.
[0236] <Example 33>
[0237] 30 parts of YUBASE4 and 133.1 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 30 parts of YUBASE4, 30 parts of n-butyl acrylate, 0.5 parts of LUPEROX575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (20 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (44.5 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic acid graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 5.
[0238] <Example 34>
[0239] 30 parts of YUBASE4 and 133.1 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 30 parts of YUBASE4, 27 parts of n-butyl acrylate, 3 parts of 4-hydroxybutyl acrylate, 1 part of LUPEROX 575 as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (20 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (44.5 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. Table 5 shows the evaluation results of the obtained friction reducing agent for lubricating oil.
[0240] <Example 35>
[0241] 10 parts of YUBASE4 and 171.0 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 30 parts of YUBASE4, 10 parts of n-butyl acrylate and 0.3 parts of LUPEROX575 as a polymerization initiator was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (45 parts) and LUPEROX575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (22.5 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic acid graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 5.
[0242] <Comparative Example 1>
[0243] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.1 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (30 parts) and 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PEROCTAO) (0.5 parts) was added dropwise over 1 hour. Then, the temperature was raised to 110° C. and maintained for 1 hour, and then 41.1 parts of YUBASE 4 was added and cooled to obtain a YUBASE 4 solution containing 35% by mass of a polymer. Table 6 shows the evaluation results of the obtained friction reducer for lubricating oil.
[0244] <Comparative Example 2>
[0245] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of YUBASE4 (25 parts), n-butyl acrylate (13 parts), lauryl acrylate (62 parts), LUPEROX 575 (0.1 parts) as a polymerization initiator, and NOFMER MSD (0.9 parts) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 6.
[0246] <Comparative Example 3>
[0247] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 72.6 parts of YUBASE4, 45 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 24.5 parts of Acrylic Ester SL, 0.5 parts of MMA, 0.03 parts of LUPEROX 26 as a polymerization initiator, and 0.15 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (60 parts) and 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PEROCTAO) (0.5 parts) was added dropwise over 1 hour. Then, the temperature was raised to 110°C and maintained for 1 hour, and then 11.1 parts of YUBASE4 was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer. Table 6 shows the evaluation results of the obtained friction reducer for lubricating oil.
[0248] <Comparative Example 4>
[0249] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 6.9 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 45 parts of n-butyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester B), 30 parts of lauryl acrylate, 0.15 parts of LUPEROX 26 as a polymerization initiator, and 0.025 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, maintained for 3.5 hours, and then a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67.5 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. Then, the temperature was raised to 110°C and maintained for 1 hour, and then 46.7 parts of YUBASE4 was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer. Table 6 shows the evaluation results of the obtained friction reducer for lubricating oil.
[0250] <Comparative Example 5>
[0251] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 6.9 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M1 obtained in Preparation Example 2, 35 parts of n-butyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester B), 40 parts of lauryl acrylate, 0.15 parts of LUPEROX 26 as a polymerization initiator, and 0.025 parts of α-methylstyrene dimer as a chain transfer agent were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after maintaining for 3.5 hours, a mixed solution consisting of YUBASE4 (42 parts) and LUPEROX 26 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67.5 parts) and PEROCTAO (0.5 parts) was added dropwise over 1 hour. Then, the temperature was raised to 110°C and maintained for 1 hour, and then 46.7 parts of YUBASE4 was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer. Table 6 shows the evaluation results of the obtained friction reducer for lubricating oil.
[0252] <Comparative Example 6>
[0253] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M6 obtained in Preparation Example 7 were added to a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, and nitrogen bubbling was performed while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.5 parts of LUPEROX 575 as a polymerization initiator, and 1.9 parts of NOFMER MSD as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixed solution of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours. After the temperature was raised to 110°C and maintained for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic graft copolymer. The evaluation results of the obtained friction reducer for lubricating oil are shown in Table 6.
[0254] [Table 1]
[0255]
[0256]
[0257]
[0258]
[0259]
[0260]
[0261] The abbreviations in Tables 1 to 6 are as follows.
[0262] SLMA: A mixture of an alkyl methacrylate having an alkyl group with 12 carbon atoms and an alkyl methacrylate having an alkyl group with 13 carbon atoms (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester SL)
[0263] ·SMA: n-octadecyl methacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name: Light Ester S)
[0264] ·LMA: Lauryl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester L)
[0265] ·MMA: Methyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester M)
[0266] · EHMA: 2-ethylhexyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name "Acrylic Ester EH")
[0267] M1: macromonomer synthesized in Preparation Example 2
[0268] M2: macromonomer synthesized in Preparation Example 3
[0269] M3: macromonomer synthesized in Preparation Example 4
[0270] M4: macromonomer synthesized in Preparation Example 5
[0271] M5: the macromonomer synthesized in Preparation Example 6
[0272] M6: macromonomer synthesized in Preparation Example 7
[0273] LA: Lauryl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name: LA)
[0274] ·EHA: 2-ethylhexyl acrylate (Mitsubishi Chemical Corporation)
[0275] BA: n-butyl acrylate (manufactured by Mitsubishi Chemical Corporation)
[0276] EA: Ethyl acrylate (manufactured by Mitsubishi Chemical Corporation)
[0277] · BMA: n-butyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylic Ester B)
[0278] Tables 2 to 6 show that the friction reducers for lubricating oils obtained in each example have low kinematic viscosity and high friction coefficient reduction effect. On the other hand, the friction reducers for lubricating oils obtained in each comparative example have high kinematic viscosity and low friction coefficient reduction effect.
[0279] Industrial Applicability
[0280] According to the present invention, it is possible to provide a polymer lubricating oil additive, a friction reducing agent for lubricating oil, and a polymer for a lubricating oil composition which has a high friction reducing effect and a low viscosity.
Claims
1. A polymer having a main chain polymer structure and a side chain polymer structure, The side chain polymer structure comprises a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms, The mass average molecular weight is 90,000 or less.
2. The polymer according to claim 1, wherein A base oil solution containing 2% by mass of the polymer is prepared, and the kinematic viscosity at 40° C. measured according to the ASTM D7279 (D445) method is 22.4 cSt or less, The base oil is API standard Group III+.
3. A polymer having a main chain polymer structure and a side chain polymer structure, The side chain polymer structure comprises a structural unit derived from an alkyl (meth)acrylate (a) having an alkyl group with 11 to 30 carbon atoms, A base oil solution containing 2% by mass of the polymer is prepared, and the kinematic viscosity at 40° C. measured according to the ASTM D7279 (D445) method is 22.4 cSt or less, The base oil is API standard Group III+.
4. The polymer according to claim 3, wherein The mass average molecular weight is less than 50,000.
5. The polymer according to claim 1 or 3, wherein The compound further contains a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group with 1 to 10 carbon atoms.
6. The polymer according to claim 1 or 3, wherein Contains a structural unit derived from a vinyl radical polymerizable monomer (m1).
7. The polymer according to claim 1 or 3, wherein It contains structural units derived from macromonomers (M).
8. The polymer according to claim 7, wherein The macromonomer (M) includes a structural unit derived from the (meth)acrylic acid alkyl ester (a) having an alkyl group with 11 to 30 carbon atoms.
9. The polymer according to claim 7, wherein The macromonomer (M) has the structure of the following formula (1), Where, X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH, Y 1 ~Y n Each independently represents a vinyl group bonded to the vinyl radical polymerizable monomer (m2) as the monomer structural unit of the macromonomer (M), excluding X 1 ~X n-1 In the case of a substituent other than , Z represents a terminal group, and n represents an integer of 2 to 10,000.
10. A friction reducer for lubricating oil, comprising the polymer according to claim 1 or 3, and a base oil.
11. A lubricating oil composition comprising the friction reducing agent for lubricating oil according to claim 10.
Citation Information
Patent Citations
Preparation of macromonomer
JP1985133007A
Production of oligomer
JP1999240854A
Polymer composition, lubricating oil additive, viscosity index improver, lubricating oil composition, method for producing polymer composition, and method for producing macromonomer
JP2022113676A
Non-metallic member thickness determination device and non-metallic member thickness determination method
JP2022143800A
Cobalt (II) chelates as chain transfer agents in free radical polymerizations
US4680352A